Chemoenzymatic Formal Total Synthesis of ent‐Codeine and Other Morphinans via Nitrone Cycloadditions and/or Radical Cyclizations. Comparison of Strategies for Control of C‐9/C‐14 Stereogenic Centers. Issue 2 (7th February 2014) - Endoma‐Arias, Mary Ann A.; Hudlicky, Jason Reed; Simionescu, Razvan; Hudlicky, Tomas
Abstract Formal total syntheses of ent‐codeine and other morphinans were accomplished from 1‐phenyl‐2‐acetoxyethane, which was subjected to enzymatic dihydroxylation by toluene dioxygenase overexpressed in Eschericia coli JM109 (pDTG601A). The resulting cis‐dihydroarenediol was coupled with a phenol derived from bromoisovanillin and a subsequent Heck reaction was used to establish the C‐13 quaternary center. Two strategies were employed to set the C‐14 center: nitrone and nitrile oxide cycloadditions to the C‐8/C‐14 olefin and a radical cyclization of an aldehyde to C‐14. Both strategies yielded tetracyclic products that were converted to known intermediates for the synthesis of ent‐codeine, ent‐codeinone, and ent‐hydrocodone. Experimental and spectral data are provided for all new compounds. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>